The microbial communities and metabolic profiles of follicular fluid in patients with premature ovarian insufficiency - Wang, Wei; Shu, Mingming; Li, Jianhua; Wang, Qihang; Zhang, Wendan; Wang, Ye; Guo, Yiming; Cheng, Yanbin; Jiang, Honghong; Song, Chunlan; Liu, Yuan; Shang, Wei (Frontiers in Endocrinology, 2025)
IntroductionPremature ovarian insufficiency (POI) is a condition characterized by ovarian dysfunction occurring before the age of 40, and its etiology is multifactorial, including genetic, immunological, infectious, environmental, and iatrogenic factors, with over half of the cases remaining unexplained. Whether the microbial communities and metabolites in follicular fluid, which is the direct microenvironment for oocyte survival, are related to POI has not been reported.MethodsIn this study, Follicular fluid samples of 26 patients with POI and 27 controls with a normal ovarian reserve were collected and analyzed using 16S rDNA sequencing and untargeted metabolomics. Conjoint analysis was performed to identify key microbial communities and metabolites that might be involved in POI.ResultsPatients with POI exhibited significant alterations in microbial richness and diversity and metabolic profile in their follicular fluid. The downregulation of ABC transporters and upregulation of the citrate cycle (TCA cycle) might be critical for the development and progression of POI. G-Rhodopseudomonas and g-Caulobacter were identified as key microbial genera, while L-aspartic acid, citrate, isoleucine, and cytidine were identified as key metabolites.DiscussionThese findings offer novel insights into the pathogenesis of POI and might pave the way for improved clinical outcomes for individuals with POI.